Публіцистика Романа Олійника-Рахманного і українське народнопоетичне слово - Погребенник, В. (Народна творчість та етнографія, 2005)
Roman Rakhmanny (1918-2002, real name Oliynyk) is famous publicist, essay writer, historian and literary critic. The author of 17 books he paid a great deal of attention to the Ukrainian folk poetic tradition. His theoretical ideas on the ethno-musicology are based on his understanding of the importance of the national Ukrainian idea. Folklore models are being analyzed by him in a context of the existentiality of Ukrainian folk, their wish for freedom, which makes Roman Oliynyk's-Rakhmanny not only a writer and publicist but a great patriot of his country. After thje Soviet occupation he moved to Canada, but his soul was always in Ukraine and his entire life was devoted to Ukrainian culture.